PENYULUHAN TENTANG BAHAYA NARKOBA DI SMAN 3 BENGKALIS - Bobi Handoko; Anastasya Shintia Yuliana; Heru Hardianto; Justika Alwi; Annisa Nurulisah (LPPM Universitas Awal Bros, 2020)
Drugs are substances or drugs either natural, synthetic, or semi-synthetic, which cause the effect of decreased consciousness, hallucinations, and stimulation. The term drug refers to a group of substances that generally pose a risk of addiction to its users. Adolescence is a transitional period between childhood and adulthood, which begins at the time of sexual maturity between the ages of 11 or 12 years to 20 years. Purpose of community service To make students know about the dangers of drugs and know about the types of drugs. The implementing method provides directions to students to stay away from drugs and other types of drugs and provides leaflets about the dangers of drugs. The obstacle that occurred during the activity process was that there were some students and students were not aware of the socialization of this activity, so they did not attend the activity. The solution is the school will give an announcement on the wall to invite directly to the school to attend this activity. The Results On Tuesday, 08.00 am to 12.00 noon, students who attended were given material related to knowledge about the dangers of drugs. This is done to help students understand about the dangers of drug abuse. At 1:00 p.m. to 4:00 p.m., the speakers explained the prevention efforts in drug abuse. Then proceed by asking again the things that have been explained about the dangers of drugs with prevention efforts. The conclusion is that students who participate in counseling on the dangers of drugs are to know what drugs are and become provisions for them later.